2021
DOI: 10.1037/hea0001108
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and perceived stress, social support, loneliness, and health in autistic adults.

Abstract: Objectives: Although the health consequences of life stress in the general population are well known, how different stressors occurring over the lifetime cause morbidity and mortality in autism is unclear, as are the factors that moderate and mediate these associations. The few studies that have compared autistic and non-autistic individuals have used instruments that yield few stress exposure indices and assess stressors occurring over short time periods. Method:To address these issues, we used the Stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 63 publications
0
23
1
Order By: Relevance
“…These studies have shown autistic females report higher levels of stress in response to events involving sensory stimuli and personal contact, relative to autistic males, and older autistic adults report greater stress than their younger counterparts for all domains except exposure to sensory stimuli and personal contact (Gillott & Standen, 2007; McGillivray & Evert, 2014). Research has also examined lifetime exposure to major stressors and perceived severity of those stressors using the Stress and Adversity Inventory for adults (STRAIN; Slavich & Shields, 2018), showing autistic adults reported greater stress responsivity overall, and in particular greater severity of stress in response to stressors characterized by change, humiliation, and physical danger (Moseley et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown autistic females report higher levels of stress in response to events involving sensory stimuli and personal contact, relative to autistic males, and older autistic adults report greater stress than their younger counterparts for all domains except exposure to sensory stimuli and personal contact (Gillott & Standen, 2007; McGillivray & Evert, 2014). Research has also examined lifetime exposure to major stressors and perceived severity of those stressors using the Stress and Adversity Inventory for adults (STRAIN; Slavich & Shields, 2018), showing autistic adults reported greater stress responsivity overall, and in particular greater severity of stress in response to stressors characterized by change, humiliation, and physical danger (Moseley et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The stress-buffering hypothesis argues that the social support protects mental health through the indirect pathway of interacting with the stressors or moderating the effect ( Cohen and Wills, 1985 ). In other words, social support may exert a direct effect by reducing the severity with which stressors are perceived, but it can also act as a buffer against the deleterious effects of stressors perception, reducing the activity of pathways that harm health ( Cohen and Wills, 1985 ; Moseley et al, 2021 ). Based on this model, social support is a buffering factor in the development of psychopathology and adjustment difficulties following experiences of a stressful event(s) ( Praharso et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bishop-Fitzpatrick et al (2018) found a significant inverse relationship between perceived stress and quality of life in a sample of adults with autism. Moseley et al (2021) found that adults with autism experienced greater perceived stress than individuals without autism and that the perceived severity of stressors was correlated with measures of both poorer physical and mental health, and less social support—all of which are determinants of quality of life. Scott and Havercamp (2014) found that perceived stress was related to poorer mental health outcomes for adults with intellectual disability in a national sample of over 10,600 individuals, and in a study of 119 individuals with multiple sclerosis (MS), Senders et al (2014) found that perceived stress was significant related to both mental and physical quality of life measures.…”
Section: Introductionmentioning
confidence: 98%